Information Technology Management for Modifying the Random S-Box Generation of AES Using Cloud - Hajer, Muatamed Abed; Obied, Ali; Taher, Bahaa Hussein (International Journal of Engineering and Technology, 2018)
The cloud computing is growing technology for IT industries. The cloud refers to a network or internet and the cloud computing refers to manipulating, configuring and accessing the software and hardware resources remotely. The attack detection is used for detecting the attack in cloud computing. It is used to prevent the data and improve the security. The cloud computing is attacked by the attackers, and among those Side Channel Attacks are most harmful. This type of attack is aimed to retrieve the secret data from the cryptographic system. This type of attacks reduces the performance of cloud computing. The attacks occur due to security issues in terms of increasing the memory spaces, high power consumption, and high execution time, reduced browsing security, and increased time complexity and error tolerances. It decreases the performances of cloud computing process. To overcome the security issues, two processes are developed. The first process developed is AES with Rijndael algorithm and the next process is effective Enriched AES (E-AES) algorithm. To increase the security, modified AES with random S-box generation is proposed in next process of the work. Data security is critical in the communication system with secure and complex cryptographic algorithms. The secret keys are used in data transmission in data management for security purposes. The effective security is provided by secure Side Channel Attack and the effective Enriched AES (E-AES) algorithm. In this phase, the E-AES algorithm is used for both encryption and decryption processes. This algorithm is used to reduce the Side Channel Attacks. The generation of random multiple S-box is made hard, to break the text that is in the encryption process which helps to manage the information technology. The proposed algorithm provides some advantages, such as, reduced time complexity, and error tolerances. It is used in varies key bits, such as, 64 bits, 128 bits, and 256 bits.